Task-biased changes of employment and remuneration: The case of occupations - Stephan Kampelmann; François Rycx (Institute for the Study of Labor (IZA), 2011)
Different empirical studies suggest that the structure of employment in the U.S. and Great Britain tends to polarise into good and bad jobs. We provide updated evidence that polarisation also occurred in Germany since the mid-1980s until 2008. Using representative panel data, we show that this trend corresponds to a task bias in employment changes: routine jobs have lost relative employment, especially in predominantly manual occupations. We further provide the first direct test for whether task-biased technological change affects employment and remuneration in the same direction and conclude that there is no consistent task bias in the evolution of pay rules. By contrast, compositional changes like the proportion of union members are clearly associated with long-term changes in the remuneration of occupations.
urn:nbn:de:101:1-201104113433
Keywords: J21; J24; J31; 330; polarisation; technological change; pay rules; occupations; inequality; tasks; Anforderungsprofil; Qualifikation; Technischer Fortschritt; Beschäftigungseffekt; Vergütungssystem; Lohnstruktur; Soziale Ungleichheit; Schätzung; Deutschland